Tracking- and scintillation-aware channel model for GEO satellite to land mobile terminals at Ku-band - Al-Saegh, Ali Mohammed; Sali, Aduwati; Jit Singh, Mandeep Singh; Ismail, Alyani (Hindawi Publishing Corporation, 2015)
Recent advances in satellite to land mobile terminal services and technologies, which utilize high frequencies with directional antennas, have made the design of an appropriate model for land mobile satellite (LMS) channels a necessity. This paper presents LMS channel model at Ku-band with features that enhance accuracy, comprehensiveness, and reliability. The effect of satellite tracking loss at different mobile terminal speeds is considered for directional mobile antenna systems, a reliable tropospheric scintillation model for an LMS scenario at tropical and temperate regions is presented, and finally a new quality indicator module for different modulation and coding schemes is included. The proposed extended LMS channel (ELMSC) model is designed based on actual experimental measurements and can be applied to narrow- and wide-band signals at different regions and at different speeds and multichannel states. The proposed model exhibits lower root mean square error (RMSE) and significant performance observation compared with the conventional model in terms of the signal fluctuations, fade depth, signal-to-noise ratio (SNR), and quality indicators accompanied for several transmission schemes.